2010
DOI: 10.1186/1471-2458-10-634
|View full text |Cite
|
Sign up to set email alerts
|

Social influences on mental health help-seeking after interpersonal traumatization: a qualitative analysis

Abstract: BackgroundDespite frequent and serious mental health problems after interpersonal traumatization, only a fraction of those affected by interpersonal violence seek formal help after the event. Reasons for this mismatch can be found in the individual help-seeking process but also in the individual's social environment. These social factors are explored based on a model describing the survivor's help-seeking process.MethodSurvivors of interpersonal traumatization and professionals providing help for this populati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
12
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 46 publications
(39 reference statements)
2
12
0
Order By: Relevance
“…Theories of help-seeking behaviour have been applied to interpersonal violence in general 14 15 and more specifically to female victims of intimate partner violence. 16 It has been emphasised that emotions (eg, shame due to being victimised), reactions and attitudes from relatives and friends, and wider social processes (eg, societal norms that lead to the acceptance of violence within an intimate partner relationship) influence the victims' help-seeking processes.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Theories of help-seeking behaviour have been applied to interpersonal violence in general 14 15 and more specifically to female victims of intimate partner violence. 16 It has been emphasised that emotions (eg, shame due to being victimised), reactions and attitudes from relatives and friends, and wider social processes (eg, societal norms that lead to the acceptance of violence within an intimate partner relationship) influence the victims' help-seeking processes.…”
Section: Introductionmentioning
confidence: 99%
“… 16 It has been emphasised that emotions (eg, shame due to being victimised), reactions and attitudes from relatives and friends, and wider social processes (eg, societal norms that lead to the acceptance of violence within an intimate partner relationship) influence the victims' help-seeking processes. 14–16 These theories of help-seeking behaviours either focus only on women or do not discuss gender. 14–16 However, interpersonal violence and help-seeking are gendered processes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Theories have been developed to better understand the help-seeking process of victims of interpersonal violence in general (Schreiber et al, 2009;Schreiber, Maercker and Renneberg, 2010) and more specifically female victims of intimate partner violence (Liang et al, 2005). Liang and colleagues suggest a process with three stages: a) problem recognition and definition, b) the decision to seek help, and c) selecting a source of support.…”
Section: Health Care System's Response To Victims Of Violencementioning
confidence: 99%
“…Though the three stages may seem to be characterized by cognitive decisions it is also underlined that feelings such as shame, fear and guilt will influence what happens, as will norms in society and attitudes from people in the victims' surrounding (Liang et al, 2005). It has been suggested that using an ecological model can be beneficial for understanding the help-seeking process and placing it in its sociocultural context (Schreiber et al, 2010;Alaggia, Regehr and Jenney, 2012).…”
Section: Health Care System's Response To Victims Of Violencementioning
confidence: 99%